Green cards and the location choices of immigrants in the United States, 1971 - 2000 - David A. Jaeger (Institute for the Study of Labor (IZA), 2006)
This paper documents where immigrants who enter the U.S. with different types of visas (green cards) choose to live initially and what determines those location choices. Using population data on immigrants from the Immigration and Naturalization Service from 1971 to 2000, matched to data on state characteristics from the Integrated Public Use Microsamples of the U.S. Census, I estimate conditional logit models with the 48 contiguous U.S. states as the choice set. Like previous researchers, I estimate that immigrants have a higher probability of moving to states where individuals from their region of birth represent a larger share of the state population, with relatives of legal permanent residents responding most to this factor. I also find that, in general, immigrants in all admission categories respond to labor market conditions when choosing where to live, but that these effects were the largest for male employment-based immigrants and, surprisingly, refugees.
Keywords: J61; J18; C35; 330; admission categories; immigrants; settlement patterns; conditional logit